Whole-body magnetic resonance imaging in inflammatory arthritis: systematic literature review and first steps toward standardization and an OMERACT scoring system - Østergaard, Mikkel; Weckbach, Sabine (The journal of rheumatology, 2017)
Whole-body magnetic resonance imaging (WB-MRI) is a relatively new technique that can enable assessment of the overall inflammatory status of people with arthritis, but standards for image acquisition, definitions of key pathologies, and a quantification system are required. Our aim was to perform a systematic literature review (SLR) and to develop consensus definitions of key pathologies, anatomical locations for assessment, a set of MRI sequences and imaging planes for the different body regions, and a preliminary scoring system for WB-MRI in inflammatory arthritis.
Gesehen am 09.04.2018